Growth Mechanism of Preferred Crystallite Orientation in Transparent Conducting ZnO:In Thin Films. Issue 10 (8th July 2015) - Wang, Mingsong; Jiang, Lingxia; Wang, Yulan; Kim, Eui Jung; Hahn, Sung Hong
Abstract : Texture engineering of thin films with controlled crystalline orientation is essential in tuning their properties. We have successfully prepared ZnO:In thin films via chemical bath deposition (CBD), with the preferred orientation of the films varying from [002] to [100] and [110] by simply altering the solvent composition. Growth mechanism of the preferred crystallite orientation in ZnO:In thin films have been systematically investigated. It is found that the variation in the preferred orientation in the films obeys the principle of evolutionary selection, that is, the fastest‐growing crystallographic direction determines the preferred orientation of the films. The tunable crystallite orientation indicates no epitaxial relationship has been established between the crystallites and the seeds. XPS analysis reveals the successful incorporation of indium in the ZnO:In thin films and the oxygen desorption upon reductive annealing. CBD, thus, is demonstrated to produce transparent conductive oxide thin films with tunable textures.